Penyuluhan tentang Cara Mengatasi Dismenorea pada Remaja Puteri di SMA Takwa Palembang - Novi Rida Eriyani (Institut Teknologi dan Bisnis Semarang, 2024)
Dysmenorrhea is considered a normal complaint experienced during menstruation. Pain arises due to contractions that occur in the uterus. These contractions function to shed menstrual blood that sticks to the uterine wall. The World Health Organization (WHO) reports globally that the incidence of dysmenorrhea is still very high. The incidence of dysmenorrhea in young women was 16.8-81% in 2018. The results of Riskesdas (2018) showed that the number of dysmenorrhea cases was 64.25%. It is estimated that as many as 90% of women in Indonesia experience menstrual pain, but do not report it to health services. The aim of this activity is to increase the knowledge of SMA Takwa Palembang students about how to deal with complaints of menstrual pain. The results of the activity showed that the average knowledge of young women had increased after the counseling activities, namely 34.8. On average, participants said they experienced menstrual pain on the first day of menstruation with varying duration of pain. It is hoped that young women will practice the knowledge gained in this activity when they feel menstrual pain.